Tipagem molecular de Streptococcus pneumoniae isolados da nasofaringe de crianças no contexto da vacinação pneumocócica - ROCHA, Cristyane Gonçalves Benicio Bastos (2010)
Objectives (i) Present review article focusing on pneumococcal vaccines and carriage; (ii) to validate sequential multiplex PCR for identifying pneumococcal capsular serotypes from children attending day-care centers; (iii) determine the multilocus sequence typing; (iv) to identify the capsular types of multiple colonies of S. pneumoniae isolates from a single sample of nasopharyngeal secretions of children attending day-care centers in Goiânia. Materials and Methods S. pneumoniae was obtained from health children less than 5 years old attending 62 day care centers of Goiânia. The laboratory procedures were performed according to WHO recommendations. Were selected 217 isolates (penicillin resistant and sensitive) for capsular typing by multiplex PCR technique. MLST was performed for 55 isolates representing the serotypes detected and the different susceptibility patterns for penicillin. Quellung reaction was used for typing isolates serotypes 6A, 6B, 18C and the isolates not typed by multiplex PCR. For 28 presumptive pneumococcal positive NP swabs, 3 colonies were picked to acess possible serotype diversity. Eighty four pneumococci were identified by conventionally procedure and multiplex PCR was performed. Results Serotypes were deduced for 177/217 (81.6%) of the pneumococcal. The most frequent serogroups/serotypes were 14, 6, 23F, 19F and 18. Multiple serotypes were detected in 13 specimens. Were found 19 MLST types and two new ST. Forty (18.4%) were not serotyped by the multiplex PCR and quellung reaction. The analysis of three colonies from the same NP permitted the detection of differente serotypes in 7/28 (25%) NP samples. Conclusion (i) The multiplex PCR is simple and cost-effective method for detecting multiple serotypes in nasopharyngeal isolates; (ii) and thus might be useful for the monitoring of pneumococcal colonization over time; (iii) the use of multiplex PCR can further broaden our understanding of the dynamics of pneumococcal carriage, including multiple serotypes, the effect of vaccination on carriage, and transmission, as well as surveillance of IPD and co-colonization.